E.Coli Bacterial Contamination and Sanitation Hygiene in Refill Drinking Water (AMIU) During the Covid-19 Pandemic - Erni, Erni; Baharuddin, Alfina; Amelia AP, A. Rizki; Multazam, Andi (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
Refill Drinking Water Depot (DAMIU) is one of the business activities that is increasing yearly, including in the Makassar City Layang Health Center Work Area. Affordable prices, which are more practical and easy to obtain, make many people consume them. This study aimed to determine the relationship between depot hygiene and sanitation implementation and the bacteriological content of drinking water in the work area of the Layang Health Center Makassar City. This research is descriptive and uses the cross-sectional approach. The sampling technique is total sampling, which takes the entire population to be sampled, so the sample in this study was 32 drinking water depots. Data was collected by observing, interviewing, and taking samples of drinking water examined at the Makassar City Health Service Laboratory. The results showed that there was a relationship between the treatment site and the bacteriological content of drinking water (p = 0.039 < = 0.05), and there was a relationship between the processing equipment and the bacteriological content of drinking water (p = 0.011 < = 0.05). There was no relationship between the handler and the bacteriological content of drinking water (p = 0.423 > = 0.05). It is suggested that the owner of the drinking water depot in the working area of the Layang Health Center pay attention to the condition of the place, equipment, and health of the handlers/managers of the drinking water depot.to produce quality drinking water that meets the requirements.